Localização de pontos quânticos semicondutores via nanolitografia por oxidação anódica - Carlos Gabriel Pankiewicz (2009)
Research on nanostrucured semiconductor heterostructures has remarkably increased over the last decades. The 1, 55 um emission wavelenght receives special attention due to its many applications for telecommunications. Recent studies have shown that InAs and InGaAs semiconductor quantum dots (QDs) grown on InP substrate are useful tools for the construction of optical devices working on that wavelenght range. However, when using the most well known quantum dot growth technnique, the Stranski-Krastanov self-assembled quantum dots technnique, the dots grow at random with no control of their site of formation whatsoever. In sight of those facts, this work was made with the objective of achieving site control of InAs and In0,53Ga0,47As semiconductor quantum dots grown on InP substrate. The Anodic Oxidation Nanolithography (AON) is used for surface patterning. Nano-sized oxide dots are made over the InP surface using an Atomic Force Microscope (AFM). Chemical removal of those oxide dots leads to the formation of pits at the site of oxidation and completes the patterning process. The pits work as nucleation sites for the semiconductor quantum dots. AFM images showed relative difficulty on InAs QD nucleation at the pre-determined sites but, on the other hand, satisfatory results for InGaAs. The perfect lattice match between InP and In0,53Ga0,47As allows partial filling of the pits, favouring QD positioning on pre-determined sites. Photoluminescence measurements are about to be carried out in order to verify the quantum dots properties of this structure.